Narrando experiências, montando ca(u)sos : análises das práticas de cuidado na saúde mental infanto-juvenil - Botelho, Ivana Carneiro (2014)
This work presents some analysis of care practices among children and adolescents in the mental health field. To do so, it undertakes the mounting cases of boys and girls who make use of some Mental Health equipment. The research stands by a "policy of narratives" that takes the narrative as a procedural diagram of experiences in the field. In this sense, the assembly of the cases is done by a procedure by tracing the care practices, giving visibility to existing policies, mapping the heterogeneous elements. In this way, discussions and problems found by some practices are made in the field of Mental Health of Children and Adolescents: the late facing with the mental health issues of childhood and adolescence; sheltering as the only way to care; the production of the Autism and specialism spaces; the guidance of a policy of Psychosocial Care; innovative devices like CAPSi; the open and public debate of care policies. We affirm that the construction of policies that are in fact public enables the invention of care practices in everyday services; in the availability of meeting with every boy and girl; in the uniqueness of the cases; processuality in the constitution of the field of action, of laws and ordinances; in social movements; in the analyzers, which bring into question the naturalized practices. This is the biggest sense of this study, a no crystallization of policy but the invention of laborious care practices.